Perancangan Interior Galeri Futsal di Surabaya - Edwin Prasetya Halim; Andereas Pandu Setiawan; dody wondo (Intra, 2015)
Futsal interior design gallery in Surabaya aim to find a lot of new and emerging futsal place in the coming future. And futsal place is always crowded with visitors and players each day. From the above facts we can see the enthusiasm of the Surabaya people upon this sport. Therefore created a futsal gallery into a facility for the people who loves the sport of futsal and for other visitors for entertainment. Futsal gallery itself provides several facilities like an information center that provides insights of the futsal sport, futsal and football history. Other than that not only to provide information only, but also in the gallery there are stores that sell futsal sports equipments such as clothes, balls, shoes. In addition there is a café for players after playing futsal to hang out. Interior design Futsal gallery is expected to answer the needs of visitors and also to provide entertainment for futsal sports lovers. So that people can not only play, but also understand the history and rules that exist in futsal. And everything related to futsal.